Recurrence Relations Definition
- Recurrence Relation Rule 1
- An equation that expresses the value of $An$ in terms of at least one previous term in a sequence.
- Recurrence Relation Rule 2
- Initial conditions must be specified to determine the value of the first term in the sequence.
Example:
$An = A(n-1)+ 2* A(n-2)$ for $n>= 2$ where $A0=2, A1=5$
Arithmetic Sequences
Given a sequence $A0, A1, A2, A3, …$, there may be an arithmetic sequence $An$ that satisfies the recurrence relation.
Example:
$An = A(n-1) + 6$ for $n>= 1$ where $A0=3$
- $A1 = A0 + 6 = 3 + 6 = 9 $
- $A2 = A1 + 6 = 9 + 6 = 15 $
- $A3 = A2 + 6 = 15 + 6 = 21 $
Notice how each sum is 6 more than the previous sum. We can create an arithmetic sequence from this recurrence relation.
$An = 6n + 3$ satisfies the recurrence relation for all values $n>= 0$ assuming $A0=3$.
Fibonacci Sequence
The Fibonacci sequence is a sequence of numbers where each number is the sum of the previous two numbers. The first two numbers in the sequence are $0$ and $1$.
- Fibonacci Sequence
- $An=A(n-1)+A(n-2)$ for $n>=2$ where $A0=0$ &$A1=1$
Solving Recurrence Relations
The best way to solve recurrence relations is to find a non-recursive formula for the sequence. Use this closed formula to calculate any value of $An$ in the sequence.
- Close Formula
- A non-recursive formula to calculate $An$ for a sequence.
Iteration Involving Substitution Method
- $An = A(n-1) + 3$ for $n>= 1$ where $A0=2$
- $A0 = 2$
- $A1 = A0 + 3 = 2 + 3 = 2+3$
- $A2 = A1 + 3 = (2+3) + 3 = 2 + 2(3)$
- $A3 = A2 + 3 = (2+3+3) + 3 = 2 + 3(3)$
- $A4 = A3 + 3 = (2+3+3+3)+3 = 2+ 4(3)$
For $An$, the sum is $2 + n(3)$ where $n>=0$ Solution: $An = 2+3n$
Iteration Without Substitution Method
- $An = A(n-1) + 3$ for $n>= 1$ where $A0=2$
- $A0 = 2$
- $A1 = A(n-1) + 3 = A(n-1) + 3$
- $A2 = (A(n-2) + 3)+3 = A(n-2) + 2(3)$
- $A3 = (A(n-3) + 2(3))+3 = A(n-3) + 3(3)$
- $A3 = (A(n-4) + 3(3))+3 = A(n-4) + 4(3)$
For $An$, the sum is $A(n-n) + n(3)$ where $n>=0$, meaning that $An = A0 + n(3)$ Solution: $An = 2+3n$